2009
DOI: 10.1016/j.aller.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Why can patients with baker's asthma tolerate wheat flour ingestion? Is wheat pollen allergy relevant?

Abstract: Diagnosis in patients sensitised to multiple pollens is difficult due to the relationship between pollen and food allergens. Misdiagnosis is often a cause for unsuccessful specific immunotherapy. Wheat is a potent allergen source and is one of the causes of baker's asthma, food and pollen allergy. Recently, we have performed a study on pollen sensitisation in our area, where cereal crops are very important. The clinical data from 19718 patients reviewed showed that grass pollen was the main source of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
185
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 8 publications
0
185
0
Order By: Relevance
“…Several studies have shown that adults with occupational asthma to a food enzyme (as described for α‐amylase from A. oryzae ) can ingest respiratory allergens without acquiring clinical symptoms of food allergy (Cullinan et al., ; Poulsen, ; Armentia et al., ). Considering the wide use of α‐amylase as a food enzyme, only a low number of case reports has been described in literature focused on allergic reactions upon oral exposure to α‐amylase in individuals respiratory sensitised to α‐amylase (Losada et al., ; Quirce et al., ; Baur and Czuppon, ; Kanny and Moneret‐Vautrin, ; Moreno‐Ancillo et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Several studies have shown that adults with occupational asthma to a food enzyme (as described for α‐amylase from A. oryzae ) can ingest respiratory allergens without acquiring clinical symptoms of food allergy (Cullinan et al., ; Poulsen, ; Armentia et al., ). Considering the wide use of α‐amylase as a food enzyme, only a low number of case reports has been described in literature focused on allergic reactions upon oral exposure to α‐amylase in individuals respiratory sensitised to α‐amylase (Losada et al., ; Quirce et al., ; Baur and Czuppon, ; Kanny and Moneret‐Vautrin, ; Moreno‐Ancillo et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Several cases of respiratory allergy following occupational inhalation of xylanase have been reported (Elms et al, 2003;Martel et al, 2010). However, some studies have shown that adults with occupational asthma to an enzyme used in food can commonly ingest the corresponding allergen without acquiring clinical symptoms of food allergy (Cullinan et al, 1997;Brisman, 2002;Poulsen, 2004;Armentia et al, 2009). In addition, only incidental cases have been described where ingestion of a-amylase led to adverse reaction in patients sensitised through the respiratory route (Baur and Czuppon, 1995;Kanny and Moneret-Vautrin, 1995;Moreno-Ancillo et al, 2004).…”
Section: Allergenicitymentioning
confidence: 99%
“…Several studies have shown that adults with occupational asthma may be able to ingest respiratory allergens without acquiring clinical symptoms of food allergy (Brisman, 2002;Poulsen, 2004;Armentia et al, 2009). Several studies have shown that adults with occupational asthma may be able to ingest respiratory allergens without acquiring clinical symptoms of food allergy (Brisman, 2002;Poulsen, 2004;Armentia et al, 2009).…”
Section: Allergenicity 18mentioning
confidence: 99%